2022
DOI: 10.1159/000528186
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors across Poorly Differentiated Neuroendocrine Neoplasms: A Pooled Analysis

Abstract: Introduction: Poorly differentiated neuroendocrine carcinomas (NECs) are characterized by aggressive clinical course and poor prognosis. No reliable prognostic markers have been validated to date; thus, the definition of a specific NEC prognostic algorithm represents a clinical need. This study aimed to analyze a large NEC case series to validate the specific prognostic factors identified in previous studies on gastro-entero-pancreatic (GEP) and lung NECs and to assess if further prognostic parameters can be i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…In the present study we chose 55% as a cut-off value for poorly differentiated PNEN. Some studies have shown that PNEN patients with a Ki-67 < 55% had a better prognosis [ 12 , 26 ]. Milione et al also showed that the Ki-67 index cutoff at 55% was a powerful predictor of over survival in patients with bronchopulmonary pure and composite large cell neuroendocrine carcinomas [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study we chose 55% as a cut-off value for poorly differentiated PNEN. Some studies have shown that PNEN patients with a Ki-67 < 55% had a better prognosis [ 12 , 26 ]. Milione et al also showed that the Ki-67 index cutoff at 55% was a powerful predictor of over survival in patients with bronchopulmonary pure and composite large cell neuroendocrine carcinomas [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research on GEP NEN shows that some features impact the survival of patients; those are Age at diagnosis, WHO performance status, Primary tumor location, Tumor morphology, Tumor differentiation, Lactate dehydrogenase (LDH), Platelets, Albumin, Ki-67, SUV max , and TNM-staging [5,[8][9][10][11][12][13][14]. Tumor differentiation is highly correlated to tumor morphology, so we do not include the feature in this work.…”
Section: Experiments 2: Feature Selection With Prior Knowledgementioning
confidence: 99%
“…The prognosis for patients with advanced GEP NEC is poor, with a median survival of less than 12 months [5,6], whilst the prognosis for locoregional GEP NEC is higher; 20.7 months [7]. Numerous recently published studies [5,[8][9][10][11][12][13][14] have shown the prognostic importance of several parameters on overall survival (OS) such as age, performance status (PS), primary tumor site, tumor differentiation, TNM-stage, serum lactate dehydrogenase (LDH), serum platelet levels, proliferation marker Ki-67, maximum standardized uptake value (SUV max ), total metabolic tumor volume (tMTV) and total total lesion glycolysis (tTLG). Establishing more robust prognostic parameters and validating established parameters is essential to provide optimal care for this patient group.…”
Section: Introductionmentioning
confidence: 99%